Policy volatility and the propensity of policies to fail: dealing with uncertainty, maliciousness and compliance in public policy-making. (24th November 2022) - Howlett, Michael; Leong, Ching
Most policy research to date has underemphasised the difficulties encountered in developing and putting policies into practice. Some of these problems are inherent to policy-making in contexts that are highly uncertain, while others arise when policy-makers act maliciously or policy-takers fail to comply with government wishes. These risks of uncertainty, maliciousness and non-compliance contribute to policy volatility (the risk of failure). The article stresses the need for improved risk management and mitigation strategies in policy formulation and policy designs if volatility is to be minimised. It sets out these three 'inherent vices' of policy-making and develops an approach borrowed from product failure management in manufacturing and portfolio management in finance to help better assess and manage policy risk.